Bistable and Reconfigurable Photonic Crystals—Electroactive Shape Memory Polymer Nanocomposite for Ink‐Free Rewritable Paper - Xie, Yu; Meng, Yuan; Wang, Wenxin; Zhang, Elric; Leng, Jinsong; Pei, Qibing (Advanced functional materials, 2018)
Paper has remained the world's most‐widely accessible information medium even as sustainable and reusable paper replacements have attracted increasing attention. Here, an ink‐free rewritable paper concept is developed that combines recent developments in photonic crystals, shape memory polymers, and electroactive polymers in a nanocomposite that matches the benefits of paper as a zero‐energy, long‐term data storage medium, but provides the additional advantage of rewritability. The rewritable paper consists of a ferroferric oxide‐carbon (Fe3O4@C) core–shell nanoparticle (NP)‐based photonic crystal embedded in a bistable electroactive polymer (BSEP). Electrical actuation induces large deformation in the z‐axis of the nanocomposite, creating distinct color change in the actuated area. This nanocomposite stores high fidelity color images without inks, the images remain stable after more than a year of storage in ambient conditions, and the stored images can then be rewritten over 500 times without degrading. A seven‐segment numerical display is also demonstrated. Ink‐free rewritable paper enabled by the interdisciplinary combination of photonic crystals, shape memory polymers, and electroactive polymer. The nanocomposite can be repeatedly triggered to change into different shapes and colors by an electric field, as well as maintain the change for a long term without energy input.